Association between functional disability with postural balance among patients with chronic low back pain - Sun, Pingge; Li, Kunbin; Yao, Xianli; Wu, Zhiyuan; Yang, Yafei (Frontiers in Neurology, 2023)
Postural balance is impaired in patients with chronic low back pain (CLBP). In addition, the swaying velocity can be affected by low back pain (LBP) dysfunction. However, the extent to which the dysfunction affects postural balance in CLBP patients remains unclear. Therefore, this study aimed to investigate the effect of LBP-related disability on postural balance among CLBP patients and determine factors associated with postural balance impairments. Participants with CLBP were recruited and instructed to complete the one-leg stance and Y-balance test. Moreover, they were divided into two subgroups (i.e., low and medium to high LBP-related disability groups) to compare the difference in postural balance based on the degree of LBP-related disability measured by the Roland Morris Disability Questionnaire. The relationships between postural balance and negative emotions as well as LBP characteristics were determined using the Spearman correlations. A total of 49 participants with low LBP-related disabilities and 33 participants with medium to high LBP-related disabilities participated in the study. Compared to the medium to high LBP-related disability group, patients in the low LBP-related disability group performed better in one-leg stance on the left leg (z = -2.081, p = 0.037). For Y-balance test, patients in the low LBP-related disability group also had greater normalized values of left leg reach in posteromedial (t = 2.108, p = 0.038) direction and composite score (t = 2.261, p = 0.026) and of right leg reach in posteromedial (t = 2.185, p = 0.032) and posterolateral (t = 2.137, p = 0.036) directions as well as composite score (t = 2.258, p = 0.027). Factors associated with postural balance impairments were also revealed, such as anxiety, depression, and fear avoidance belief. In conclusion, the greater the dysfunction degree, the worse the CLBP patient’s postural balance impairment. Negative emotions could also be considered contributing factors for postural balance impairments.